Integration of Endocannabinoid and Leptin Signaling in an Appetite-Related Neural Circuit - Jo, Young-Hwan (2005)
Recently developed therapeutics for obesity, targeted against cannabinoid receptors, result in decreased appetite and sustained weight loss. Prior studies have demonstrated CB1 receptors (CB1Rs) and leptin modulation of cannabinoid synthesis in hypothalamic neurons. Here, we show that depolarization of perifornical lateral hypothalamus (LH) neurons elicits a CB1R-mediated suppression of inhibition in local circuits thought to be involved in appetite and “natural reward.” The depolarization-induced decrease in inhibitory tone to LH neurons is blocked by leptin. Leptin inhibits voltage-gated calcium channels in LH neurons via the activation of janus kinase 2 (JAK2) and of mitogen-activated protein kinase (MAPK). Leptin-deficient mice are characterized by both an increase in steady-state voltage-gated calcium currents in LH neurons and a CB1R-mediated depolarization-induced suppression of inhibition that is 6-fold longer than that in littermate controls. Our data provide direct electrophysiological support for the involvement of endocannabinoids and leptin as modulators of hypothalamic circuits underlying motivational aspects of feeding behavior.